Interferometric rotating point spread function - Wei Wang (Nature Portfolio, 2017)
Abstract Rotating point spread functions (PSF), such as the double helix (DH) PSF, are widely used in localization-based super-resolution imaging because of their large working depth range. In this article, we propose an interferometric DH PSF (iDH PSF) using two opposed objective lenses as in the 4Pi microscope. In the proposed iDH PSF, the super-resolution in the axial PSF is transferred to the azimuthal rotation. Moreover, we design an iDH PSF whose imaging range reaches 3 μm, which is roughly 3 times as much as that which can be obtained by using other interferometric localization-based super-resolution imaging methods.